2004
DOI: 10.1007/s00425-004-1447-7
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis SERK1 protein interacts with the AAA-ATPase AtCDC48, the 14-3-3 protein GF14λ and the PP2C phosphatase KAPP

Abstract: Leucine-rich repeat (LRR)-containing transmembrane receptor-like kinases (RLKs) are important components of plant signal transduction. The Arabidopsis thaliana somatic embryogenesis receptor-like kinase 1 (AtSERK1) is an LRR-RLK proposed to participate in a signal transduction cascade involved in embryo development. By yeast two-hybrid screening we identified AtCDC48, a homologue of the mammalian AAA-ATPase p97 and GF14lambda, a member of the Arabidopsis family of 14-3-3 proteins as AtSERK1 interactors. In vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 44 publications
4
67
0
1
Order By: Relevance
“…All of the interacting 14-3-3 proteins localize to both the nucleus and the cytosol. 14-3-3 proteins were also shown to interact with BAK1, its homolog SERK1, and the barley (Hordeum vulgare) homolog Hv BAK1 (Rienties et al, 2005;Karlova et al, 2006;Schoonheim et al, 2007), further supporting important roles of 14-3-3 proteins in BR signaling. 14-3-3 binding has recently emerged as a key regulatory mechanism in plant signaling as well as in yeast and animal systems.…”
Section: Discussionmentioning
confidence: 81%
“…All of the interacting 14-3-3 proteins localize to both the nucleus and the cytosol. 14-3-3 proteins were also shown to interact with BAK1, its homolog SERK1, and the barley (Hordeum vulgare) homolog Hv BAK1 (Rienties et al, 2005;Karlova et al, 2006;Schoonheim et al, 2007), further supporting important roles of 14-3-3 proteins in BR signaling. 14-3-3 binding has recently emerged as a key regulatory mechanism in plant signaling as well as in yeast and animal systems.…”
Section: Discussionmentioning
confidence: 81%
“…In a previous study it was demonstrated using a yeast-two hybrid assay that a leucine rich receptor (LRR) somatic embryogeneis receptor (SERK1) interacts with cell division cycle 48 (CDC48) and with 14-3-3λ (Rienties et al, 2005). CDC48 is expressed throughout the plants in regions of cell division such as the vegetative shoot, root, floral inflorescence and flowers, and in rapidly growing cells (Rienties et al, 2005). 14-3-3 has also been shown to regulate activity of mitochondrial and chloroplast F 0 F 1 ATP synthase via a phosphorylation-dependent binding.…”
Section: Discussionmentioning
confidence: 99%
“…Tensile strength tests suggest its high cell density results in increased cellulose content but the cell wall architecture in 14-3-3λ mutants is altered and, hence emphasizes its role in cell wall development. This gene has a pivotal role in maintaining integrity of plant cells during drought stress particularly since it has been shown to interact with cell division genes such as CDC 48 and SERK1 (Rienties et al, 2005). The collapse of the epidermal, endodermal and cortex cells in the roots of the 14-3-3 mutants also provide evidence of its role in root development.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Arabidopsis 14-3-3 λ was known to interact with a putative peroxisomal ascorbate peroxidase APX3, which is an enzyme that scavenges H 2 O 2 to prevent cell damage from this reactive oxygen species, and AKR2, an ankyrin repeat-containing protein that is probably involved in antioxidation metabolism (Yan et al, 2002). In addition, it was shown that this 14-3-3 protein interacted with SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KIN-ASE (SERK1) (Rienties et al, 2005). SERK1 is a very important component in brassinosteroid signaling in combination with BAK1, another receptor-like protein kinase, which plays a critical role in PTI induction in Arabidopsis with other PRRs such as FLS2 and EFR (Zipfel, 2008).…”
Section: Involvement Of 14-3-3 Proteins In Plant Immunitymentioning
confidence: 99%